Treatment options for rheumatoid arthritis beyond TNF-α inhibitors. Issue 5 (September 2010) - Yazici, Yusuf; Simsek, Ismail
The treatment of rheumatoid arthritis has changed over the last 15 years. Early and aggressive treatment, use of methotrexate as the anchor drug and combination treatment, with older disease-modifying drugs or biologics, have become the norm. TNF inhibitors were the first biologic agents available to rheumatologists and are still currently used as first-line biologics, in addition to other newer biologic agents. Abatacept, rituximab and tocilizumab are available biologics that use a different mode of action to TNF inhibitors, and can be used after a TNF inhibitor is tried. Abatacept is also currently used as a first-line biologic and others can also be used once data are available.